IMMUNOGENIC FACTORS OF THE BREAST MILK DURING ITS PROLONGED STORAGE UNDER LOW TEMPERATURES - E. I. Kondrat'eva; D. E. Khapacheva; A. I. Tlif; L. A. Podporina; S. V. Storozhuk ("Paediatrician" Publishers LLC, 2013)
The data on the influence of the prolonged low temperatures effect (-20°C) on the immunogenic factors of the breast milk is shown in the article. The received during the study new data on the stability of the secretory immunoglobulin A in the breast milk under the low temperatures are analyzed. The influence of the low temperatures on the breast milk concentration of the certain cytokines (tumor necrosis factor , interleukins 8, 10, 18) when storing in the refrigerator for 3 and 6 months was studied. The breast milk concentration of the interleukins 8 and 18 was determined for the first time. The fact of the tumor necrosis factor a decrease during prolonged storage was established. The received results suggest that protective factors of the breast milk are preserved under low temperatures in domestic conditions, which allows to recommend the further development of breast milk storage techniques in domestic conditions and opens the prospects for the breast milk banks.